Optimization of Teak Wood Furniture Production Using Linear Programming Method at Sumenep East Java Indonesia - Siti Nurul Afiyah; M. Syaifuddin; Nur Lailatul Aqromi; Darshil Makwana (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
3R Furniture company produces some products i.e. doors, chairs, cabinets, tables and frames. This company has some problems about maximize the production and minimize the cost of production. The 3R furniture company has not managed demand properly because it has not been able to synchronize the company's available resources with fulfilling consumer demand. This study aims to determine the amount of production produced by the "3R" Furniture Company by utilizing available resources and to find out the maximum profit obtained by the "3R" Furniture Company in Sumenep Regency. This research was carried out at the "3R" Furniture Company in Sumenep Regency, especially on Kangean Island. Linear programming is a model of operational research that usually used to solve optimization problem. The simplex method is a method that can be used in linear programming which serves to find solutions optimal. The purpose of this research is to optimize the benefits of 3R Furniture company. The respondents consisted of 4 people, namely 1 business owner and 3 labor representatives from the "3R" Furniture business. The results showed that the number of products produced to obtain maximum profit was 30 units of tables by utilizing existing resources. The maximum profit by producing a table is Rp. 20999.998.